The Mediating Role of Internalizing Problems Between Peer Victimization and Dating Violence Victimization: A Test of the Stress Generation Hypothesis - Smith, Kevin (Journal of interpersonal violence, 2022)
Peer victimization and dating violence are highly prevalent among adolescents. Those two forms of victimization are notably associated with heightened levels of internalizing problems. The stress generation hypothesis stipulates that depressive cognitions and behaviors may generate interpersonal stressors for depressed individuals. It has thus been hypothesized that victims of peer victimization may experience higher levels of internalizing problems, which in turn, may render them more at risk of experiencing dating violence victimization. We used a longitudinal design with three waves from the Quebec Youth?s Romantic Relationships Survey (n = 4,923). Participants (59.6% girls, aged between 14 and 18 years old) reported their experiences of dating violence victimization, peer victimization and psychological distress. A cross-lagged panel analysis was performed to test the mediational effect of psychological distress between peer victimization and dating violence while controlling for age and gender. The interaction effect of gender in the model was also tested. The longitudinal relationship between peer victimization and dating violence victimization was significantly mediated by internalizing problems. This result thus supports the stress generation hypothesis. No interaction effect of gender was observed in the model, thus suggesting that this relationship does not change as a function of gender. This study offers to practitioners in the area of prevention and intervention for peer victimization and dating violence a different way of tackling the problem of revictimization. Indeed, our findings revealed that internalizing problems were longitudinally associated with subsequent relational problems, when occurring after being victimized. Therefore, addressing internalizing problems instead, or in addition to prevention or intervention efforts to stop victimization may help in reducing revictimization rates.